Pola Konsumsi Air Untuk Kebutuhan Domestik Pada Perusahaan Daerah Air Minum (PDAM) Di Kecamatan Manyaran Kabupaten Wonogiri - Kusumo, Bondan Jati, Drs. Yuli Priyana, M.Si (2016)
This research was conducted in district Manyaran Wonogiri Regency. This research aims to (1) determine the availability of water in the Area of drinking water CompanyGiri Tirta, (2) determine the patterns of water consumption for domestic needs and (3) determine the patterns of water consumption for domestic needs based on the social economy. Method of data collection used is stratified random sampling. Samples taken is 105 respondents. Stages of research include: a) observation (review of the literature and previous research) and administrative maps, b) survey c) processing and data analysis, d) results (analysis of the availability of water, patterns of water consumption for domestic needs, patterns of water consumption for domestic needson the basis of social economy). The availability of water in PDAM Giri Tirta comes from Springs Umbul Umbul Teleng and Nogo. The resulting discharge in December 2015 from the fountain of the Dragon have a debit of Umbul Nogo 2.5 lt/s or around 216,000 lt/day. To debit from the Umbul Teleng is 9 lt/s or approximately 777,600 lt/day. Use for domestic needs include: drinking, cooking and washing the kitchen tools, washing clothes, washing of motorcycles and cars, watering plants, and usage for the needs of others with an average amount of usage was 89.28 lt/prs/day. Test the relationship between water needs with this type of work has influence of 14.1%. This shows that influence water consumption patterns towards work very closely. Test the connection between the needs of water with levels of education have an effect of 0.3%. This suggests that the influence of educational level against water consumption patterns is less influential. Test the connection between the needs of water with levels of income have influence of 85,7%. This suggests that the influence of level of income against water consumption patterns very closely. The level of social economic effect on water consumption patterns is the level of income. On the second order the most effect on water consumption patterns is the type of job. And the latter less influence on patterns of water consumption was the level of education. Water is the most widely used comes from the ADWC, the second use of ADWC + the well, then the last of the wells.